2012
DOI: 10.1083/jcb.201112083
|View full text |Cite
|
Sign up to set email alerts
|

Human telomeres replicate using chromosome-specific, rather than universal, replication programs

Abstract: Human telomere replication initiates either from within telomere repeats or from within the subtelomere using a chromosome-specific replication program that appears conserved between different cell types.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
69
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(74 citation statements)
references
References 49 publications
(89 reference statements)
3
69
2
Order By: Relevance
“…Both results suggest that the subtelomeric region is important for controlling telomere replication timing, and, thus, a regulatory factor may be located within this specific region. This hypothesis is supported by a recent study that showed that the initiation of telomere replication occurs predominantly within the subtelomere or a region upstream of the subtelomere37. Our study confirms the role of subtelomere sequences in regulating telomere replication timing and furthermore, strongly supports the conclusion that neither centromeres nor other chromosomal sequences play a role in this process, and finally, that subtelomere sequences may be sufficient to determine telomere replication timing.…”
Section: Discussionsupporting
confidence: 89%
“…Both results suggest that the subtelomeric region is important for controlling telomere replication timing, and, thus, a regulatory factor may be located within this specific region. This hypothesis is supported by a recent study that showed that the initiation of telomere replication occurs predominantly within the subtelomere or a region upstream of the subtelomere37. Our study confirms the role of subtelomere sequences in regulating telomere replication timing and furthermore, strongly supports the conclusion that neither centromeres nor other chromosomal sequences play a role in this process, and finally, that subtelomere sequences may be sufficient to determine telomere replication timing.…”
Section: Discussionsupporting
confidence: 89%
“…This observation implies that in some cases initiation of DNA replication occurs at the telomeres. Similar observations have been reported for telomeric DNA in Xenopus cell free extracts [49] and specific telomeres of individual human chromosomes in embryonic stem (ES) cell lines and two primary somatic cell types [50]. No bubble arc was observed for the 3284 bp PvuI-PvuI DNA fragment hybridized with L2 (see Figures 1 and 5), indicating that replication does not initiate at telomeric repeats in the circular pYAC_MEM.…”
Section: Discussionsupporting
confidence: 82%
“…Telomerase is predicted to be recruited to backtracked replication forks resulting from stalling, which has been proposed to occur at measurable frequencies in telomeric DNA (Miller et al, 2006; Drosopoulos et al, 2012). Such backtracked forks will expose single-stranded leading strand TG (1-3) repeat sequence DNA, which is the substrate for telomerase elongation.…”
Section: Discussionmentioning
confidence: 99%
“…Telomeres are composed of sequence-specific DNA binding proteins bound to highly repetitive DNA sequences and are increasingly recognized as genomic regions prone to replication stress (Miller et al, 2006; Sfeir et al, 2009; Drosopoulos et al, 2012). Without the telomeric DNA-elongating enzyme telomerase, progressive telomere shortening eventually causes the collapse of the protective DNA-protein complex (deprotection), but this occurs only after many cell divisions, L ate after T elomerase I nactivation (LTI).…”
Section: Introductionmentioning
confidence: 99%